With or without ancestors? Validity of the ancestral in the Peruvian Amazon - Mouriès, Thomas (2014)
The existence —or not— of the concept of ancestors in the indigenous Amazon has been the subject of much debate. However, regional leaders do not hesitate to call upon ‘ancestral’ knowledge, customs, or territories in the sense that, from an academic point of view, could appear enigmatic. «Ancestral, but… with or without ancestors?» is the question a confused anthropologist might ask. In this article, I propose to offer elements of a response to this question,based on a case study in Peru. First I analyze how Amazonian indigenous leaders, following international law, have adopted the legal notion of ‘ancestral possession’ of their territory to adapt it to the political sphere. This approach accounts for the recent generalization and uniformization of the term ‘ancestral’, but poses the problem of how it articulates with the indigenous cosmologies that it supposes to reflect. For this reason, I explore in the second section the pertinence of the category of ‘ancestor’ in the indigenous Amazon, briefly drawing upon the academic debate in order to define inwhat way this category takes on meaning. Based on testimony from an experienced Awajún leader, we thus return in the third section more explicitly to the different meanings and planes of reference that unfold when one uses the term ‘ancestral’, showing how Amazonian indigenous people not only adopt external conceptual elements and arguments, but also transform them based on their own cosmological singularities and political perspectives.